Transwar Art in Japan. Issue 6 (2nd November 2022) - Kunimoto, Namiko
Abstract: This article focuses on the question of periodisations in Japanese art history through a consideration of the long-running careers of four successful but politically and aesthetically diverse artists: Domon Ken (1909‒1990), Okamoto Tarō (1911‒1996), Yoshihara Jirō, and Katsura Yuki (1913‒1991). The arc of these artists careers across the prewar, war, and postwar periods upsets popular periodisations in Japan's art history that assert the postwar as a time of rupture and renewal. My focus is meant to challenge this 'postwar paradigm' while elucidating these artist's negotiation of ethics and plurality during drastically different political eras. How does a reading of their work reveal continuities before and after the war, and what are the political stakes of these continuities?